Political Rights Of Former Corruptors In View Of The Constitution - Nurita, Riski Febria; Rafid, Rahmad; Fanani, Ahmad Daniyal; Perdana Bayu Putra, Rizky (International Journal of Sustainable Law, 2024)
The Supreme Court (MA) ordered the General Election Commission (KPU) to revoke Article 11 paragraph (6) and Article 18 paragraph (2) of KPU regulation (PKPU) Number 10 of 2023. Some feel the order violates human rights because it deprives a person of the political right to be elected to public office. The Supreme Court in decision Number 28 P/HUM / 2023 has granted the application for Material Test against Article 11 paragraph (6) and Article 18 paragraph (2) of PKPU Number 10 of 2023. The PKPU is considered contrary to Article 240 paragraph (1) letter g and Article 182 letter g of the election law because it provides a red carpet for former corruption convicts to become election participants. revocation of political rights is done because the convict has abused his authority as a public official, this punishment is expected to protect the public from similar actions and cause a deterrent effect for the convict. Whereas, for Contra-groups, denial of revocation of Rights is chosen or chosen because it violates human rights. This research includes library research, which is a research conducted by reading books, literature and examining various theories and opinions that have a relationship with the problem under study. In this case the author reads and takes theories from books related to issues of Political Rights and establishing laws and concludes the results of research from various kinds of such books. Judging from its nature, this study includes normative juridical Law Research. The form of normative juridical research is legal research conducted by researching library materials. This research is conducted or submitted only on Written regulations or other legal materials.